2021
DOI: 10.1136/bmjoq-2021-001493
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for recommendations after perioperative sentinel events

Abstract: BackgroundThe recurrence of sentinel events (SEs) is a persistent problem worldwide, despite repeated analyses and recommendations formulated to prevent recurrence. Research suggests this is partly attributable to the quality of the recommendations, and determining if a recommendation will be effective is not yet covered by an adequate guideline. Our objectives were to (1) develop and validate criteria for high-quality recommendations, and (2) evaluate recommendations using the criteria developed.Methods(1) Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Literature suggests SE investigators typically avoid these types of interventions. 33 , 36 Because the aggregated cross-hospital GAM analysis recommendations are based on multiple SEs from various hospitals, they may provide more relevance and urgency than case-specific recommendations. In turn, this could help to mobilize the appropriate resources to implement and follow-up on recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature suggests SE investigators typically avoid these types of interventions. 33 , 36 Because the aggregated cross-hospital GAM analysis recommendations are based on multiple SEs from various hospitals, they may provide more relevance and urgency than case-specific recommendations. In turn, this could help to mobilize the appropriate resources to implement and follow-up on recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…18,35 These types of recommendations are considered to be weak. Bos et al 36 confirmed this finding regarding generally weak recommendations, as they concluded that the majority of recommendations in 115 Dutch SE reports did not meet quality criteria and thus may have limited effect in improving patient safety. On the other hand, aggregate cross-hospital GAM analysis helped to formulate more system-oriented recommendations aimed at solving recurring issues across events and organizations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation